Opportunities to Regulate Production and Use of Disposable Plastic Items in Russia - V. A. Eremkin; D. A. Epifanov (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The article discusses the acute problem of regulating the turnover of disposable plastic items in the Russian Federation. The goal of elaborating the system of manufacturing, recycling and utilizing plastic goods is connected with the necessity to improve ecological security and to combat locating huge volumes of solid municipal waste at landfill sites in the country, the majority of them are already overfilled and their extension is not possible. In 2019 the President of Russia set the goal of developing the system of recycling and utilizing wastes, however large-scale solutions have not been implemented yet. Economic policy developers often interpret this task as the necessity to impose fines on manufacturing and turnover of certain types of disposable goods and packages, which is not always effective. The article underlines the importance of the problem, researches and systematizes approaches, which can be used to shape economic policy in Russia. Apart from that, it describes alternative opportunities of reducing volumes of wastes difficult for extraction during sorting, which should be included in the system providing closed cycle manufacturing, which is not finished with product shipping but requires waste recycling.